Higher Apnea-Hypopnea Index (AHI) and Oxygen Desaturation Index (ODI) Were Independently Associated with Increased Risks of Hypertension in Patients with T2DM: A Cross-Sectional Study - Weijuan Su; Guobing Chen; Danyan Ma; Jinyang Zeng; Fangfang Yan; Xiaoyan Lin; Ziqing Xu; Shuyu Yang; Zhibin Li; Changqin Liu (International Journal of Hypertension, 2021)
Objective. The current study aimed to explore the relationship between OSAS and hypertension and whether polysomnography (PSG) indices were independently associated with hypertension in patients with type 2 diabetes (T2DM). Methods. This study recruited 316 T2DM patients. Multivariable logistic regression analyses were performed to determine the independent association of apnea-hypopnea index (AHI) and oxygen desaturation index (ODI) with hypertension with adjustment for potential confounders. Results. Among 316 patients, 130 (41.1%) and 204 (64.6%) had hypertension and OSAS, respectively. T2DM patients with hypertension showed significantly increased levels of AHI ((median (interquartile range)): 17.2 (5.7–34.9) vs. 5.7 (2.1–17.3) events/hour, p < 0.001), nonrapid eye movement AHI (NREM-AHI) (17.6 (5.5–36.5) vs. 5.2 (2.2–16.6) events/hour, p < 0.001), ODI (48.4 (21.9–78.0) vs. 22.6 (10.8–48.1) events/hour, p < 0.001), and severities of OSAS and decreased levels of lowest SaO2 ((mean ± standard deviation): 74.0 ± 10.4 vs. 77.3 ± 9.8, p = 0.004). Multivariable logistic regression analysis showed that higher levels of AHI, NREM-AHI, and ODI were significantly associated with increased risks of hypertension, and the adjusted odds ratios (ORs) with 95% CI were 1.026 (1.008–1.044, p = 0.004), 1.026 (1.009–1.044, p = 0.003), and 1.005 (1.001–1.010, p = 0.040), respectively. Compared with non-OSAS, severe OSAS was significantly associated with the risk of hypertension with the adjusted OR (95% CI) of 3.626 (1.609–8.172, p = 0.002), but associations of rapid eye movement AHI (REM-AHI) and lowest SaO2 with hypertension were not statistically significant. Conclusion. Increased AHI, NREM-AHI, ODI, and severities of OSAS were significantly associated with higher risks of hypertension in T2DM patients. Detection and treatment of OSAS are needed to prevent hypertension in T2DM patients.